Augmenting De Ketele’s model for university pedagogy - Loisy, Catherine; Lameul, Geneviève (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2017)
As higher education undergoes major changes (mass higher education, ICT development, etc.), there is a need for methods and models that can be used to analyze the complexity of university pedagogy. In this paper, De Ketele’s model (2010) is used as the basis for two case studies. The objectives are to enrich the “field of university pedagogy” by situating ICT among the components that De Ketele describes. The case studies confirm the necessity of viewing university education as a system. They also enrich the model in three respects, namely: 1) by considering ICT a component unto itself that should be added to the model; 2) by considering educational research a full-fledged component that should be associated with ICT in the model; and 3) by reconsidering the complexity of interrelations between the components. The conclusion is that ICT leads to the pedagogical question, that further research is needed, and that the words “digital” and “pedagogy” must be associated in higher education.